2020
DOI: 10.1177/1559827620905775
|View full text |Cite
|
Sign up to set email alerts
|

Using the SMART-EST Goals in Lifestyle Medicine Prescription

Abstract: Lifestyle modifications can effectively decrease chronic disease risk but studies show little to no time during patient encounters is spent on lifestyle medicine counseling. The SMART-EST goal framework facilitates both a rich discussion of lifestyle medicine and a comprehensive patient-centered action plan for health behavior change. The tenets of the SMART-EST goal-setting process are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…[14][15][16]28 In particular, the use of the SMART technique is encouraged, where participants choose goals which are specific, measurable, achievable, relevant, and time-bound. 35 While there has been limited research in evaluating the effect of CTs in the adult primary care setting in the US, this study showed that there were a number of participants who found the CT to be helpful in achieving either a specific health goal or HRSN. However, many agreed that it was not enough to have a significant impact.…”
Section: Discussionmentioning
confidence: 75%
“…[14][15][16]28 In particular, the use of the SMART technique is encouraged, where participants choose goals which are specific, measurable, achievable, relevant, and time-bound. 35 While there has been limited research in evaluating the effect of CTs in the adult primary care setting in the US, this study showed that there were a number of participants who found the CT to be helpful in achieving either a specific health goal or HRSN. However, many agreed that it was not enough to have a significant impact.…”
Section: Discussionmentioning
confidence: 75%
“…Based on review of the narrative feedback by authors SJ and JA, students valued having formal nutrition education, recognising its clinical relevance. They appreciated learning how to approach conversations about diet in a non‐judgemental manner and specific strategies to use during counselling, including 24‐hour diet recalls and SMART goals 14,15 . For course improvement, students desired additional didactics on specific evidence‐based diets, more opportunities to practice counselling with standardised patients and spacing out the curriculum to engage with learning materials throughout the 6‐week clerkship.…”
Section: Discussionmentioning
confidence: 99%
“…After further meeting specific content (see Supplement Table 1 for details) was shared, the SMART approach to goal setting was explained so that participants could develop goals which were specific, measurable, attainable, relevant, and time-bound [ 18 ]. Participants then broke into pairs and were given 10 minutes to share with one another: (1) The steps they had taken so far in adopting a WFPB diet, (2) Setting their own personal goals to implement by the next meeting (using the SMART methodology), and (3) Possible obstacles which they might encounter.…”
Section: Methodsmentioning
confidence: 99%